Perlindungan Hukum Bagi Perempuan Dalam Perspektif Hukum Islam - Nuraini1234; fadila, dea; amelia, bela; berutu, linda; sakina, dini (Tabayyun : Journal Of Islamic Studies, 2023)
Discussions are taking place on Islamic legal viewpoints and women's role in politics. When it came to the prospect of a female president in Indonesia, Islamic political groups were adamant in 1999; however, they have since "revised" their stance. Through a variety of positive strategies, they attempt to legitimate women's leadership within a nation. It is crucial to undertake research on women's leadership from the standpoint of siyasah fiqh in light of this situation. Descriptive analysis is combined with qualitative approaches in this study.In this study, secondary data was gathered from relevant documents or files, whilst primary data was gathered through observations of activities and phenomena. Despite disagreements on this point, the research indicates that, according to the Islamic perspective, women pursuing leadership roles should have the right to be picked and chosen. Regarding women's leadership in politics, there are various fiqh siyasah points of view. The majority of the classical Sunni Siyasah Syar'iyah Ulama, such as Imam Al-Ghazali, require men, although some do not, such as al-Mawardi and Ibn Tarmiyah.